Queering Gender, Sexuality, and Becoming-Human in Qing Dynasty Zhiguai - Whyke, Thomas William. author. aut Link
XIV, 246 p. 1 illus.
Keywords: “What can we learn from classical Chinese short stories about nonhuman relationships, about gender, sexuality, and desire? How can queer theory benefit from a global historical perspective? This innovative study brings together nuanced reading of classical Chinese texts and sophisticated theoretical discussion. It asks vital questions such as what queerness is, why Chinese historic literatures matter to queer theory, and how animals, ghosts, spirits can haunt contemporary queer theorisation. It compels us to rethink how we can relate to the world less hierarchically, more ethically, and in intimate – and indeed queer – entanglements.” - Hongwei Bao, author of Queer China: Lesbian and Gay Literature and Visual Culture under Postsocialism “Shape-changing animals, un-wooable swordswomen, gender-fluid beings, sex-hungry ghosts, supernatural shadows avenging past lives, cannibalism, and pornographic ‘perverts’- Qing Dynasty zhiguai boasts them all. Insightfully reading ‘against the grain,’ this book offers analysis of the teeming intersectional potentialities undergirding Qing-era literature and identity, and how these weirdly resonate with contemporary becomings and culture.” - David H. Fleming, author of Chinese Urban Shi-nema This book offers queer readings of Chinese Qing Dynasty zhiguai, ‘strange tales’, a genre featuring supernatural characters and events. In a unique approach interweaving Chinese philosophies alongside critical theories, this book explores tales which speak to contemporary debates around identity and power. Depictions of porous boundaries between humans and animals, transformations between genders, diverse sexualities, and contextually unusual masculinities and femininities, lend such tales to queer readings. Unlike previous scholarship on characters as allegorical figures or stories as morality tales, this book draws on queer theory, animal studies, feminism, and Deleuzian philosophy, to explore the ‘strange’ and its potential for social critique. Examining such tales enriches the scope of historic queer world literatures, offering culturally situated stories of relationships, desires, and ways of being, that both speak to and challenge contemporary debates. Thomas William Whyke is an Assistant Professor at the University of Nottingham, Ningbo China. Melissa Shani Brown is affiliated with the Faculty of East Asian Studies, Ruhr-Universität Bochum, Germany.